Withdrawal of A Motor Fiduciary Guarantee Vehicle by Financing Companies against The Debtors Experienced Loss of Loans (Study of Decision Number : 50/Pdt.G/2018/PN.Plk) - Anggo Doyoharjo (East Asian Journal of Multidisciplinary Research, 2022)
The results of the study indicate that the issue of motor vehicle withdrawals by finance companies is against debtors who experience bad credit with fiduciary guarantees. Decision Number: 50/Pdt.G/2018/PN.Plk. The defendant as of March 12, 2015 until this case has permanent legal force and until it is carried out, for example the calculation of arrears in installments is in arrears from March 20 to March 31, 2015 = 20 days, so Rp 7,970,000 x 0.2 % = 15,940 x 20 days totaling Rp 318,800,-, so that the Defendant's responsibility is to pay a late fine of 0.2% every day starting from March 12, 2015 until this case has permanent legal force and is implemented. Based on the evidence from the letters and statements of witnesses, it is evident by law that the Defendant is bound by a lease agreement with the Plaintiff and the Defendant has an obligation to pay the lease installments to the Plaintiff for 48 months from October 12, 2013 to September 12, 2017, but the Defendant only fulfilled the obligation to pay installments for 17 months, the last installment was in February 2015, from March 2015 until the maturity date of September 12, 2017 did not pay installments, so that the Defendant only partially fulfilled his achievements/obligations. The legal consequence is the Verstek Decision, because the Defendant was never present at the trial even though he had been legally and properly summoned. The Defendant paid the late fee based on the Lease Financing Agreement and the Plaintiff's lawsuit was registered at the Palangka Raya District Court until the decision was final and binding.